Application of the improved multi-electrode electrical exploration methods for groundwater investigation in Vientiane Province, Laos - Minh Duc Vu; Viengthong Xayavong; Chung Anh Do; Luan Thanh Pham; David Gómez-Ortiz; Ahmed M. Eldosouky (Journal of Asian Earth Sciences: X, 2021)
The purpose of this study is to evaluate the effectiveness of the multi-electrode electrical resistivity methods and to better understand the aquifers in Laos. The improved multi-electrode electrical exploration (IMEE) methods and a SuperSting R8/IP system with 56 electrodes have been used to measure ten 2D-electrical resistivity and three induced polarization profiles, of maximum length 550 m, at four sites in the Phonhong and Thoulakhom districts of Vientiane province, Laos. The results revealed moderate resistivity regions (18–80 Ohm m) that correspond well with low chargeability values (0–21 ms) at depths from 22 to 100 m, indicating possible suitable layers of good quality groundwater. These results agree well with data from borehole 1 drilled in the Phonhong district, which indicated the location of the water table at 20 m depth where samples extracted from the drill cores have been identified as gravel and siltstone. Analyses of water samples from different existing and new wells in the survey areas, including Total dissolved solids (TDS), Electrical conductivity (EC) and pH, revealed mean values lower than the contamination thresholds, confirming that the water is suitable for drinking without causing health risk. The obtained results provide new information leading to a better understanding of the structural framework of the study area. These results also demonstrate that the IMEE methods may be an efficient tool for groundwater investigation in Vientiane Province, Laos, and these methods can be applied for groundwater exploration all over the world.